2020
DOI: 10.1590/1806-9282.66.s2.48
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and acute myocarditis: current literature review and diagnostic challenges

Abstract: SUMMARY INTRODUCTION In the current literature, there has been an upsurge of cases of COVID-19-induced acute myocarditis. In this case-based review, we aimed to describe the clinical characteristics, imaging findings, and in-hospital course of acute myocarditis. In addition, the limitations of the myocarditis diagnosis were discussed since only fulminant myocarditis cases have been mentioned in the current literature. METHODS We performed a review of the literature of all patients who were diagnosed with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 15 publications
1
12
0
2
Order By: Relevance
“…The finding of increased QRS duration and QTc interval in patients with COVID‐19 pneumonia is consistent with other studies (Antzelevitch, 2005; Bertini et al., 2020; Çınar et al., 1992).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The finding of increased QRS duration and QTc interval in patients with COVID‐19 pneumonia is consistent with other studies (Antzelevitch, 2005; Bertini et al., 2020; Çınar et al., 1992).…”
Section: Discussionsupporting
confidence: 92%
“…Yenerçağ et al and M. Öztürk F et al have shown a significant increase in TDR(Tp‐e interval and Tp‐e/QTc) in newly diagnosed COVID‐19 patients compared to controls. (Çınar et al., 1992; Yenerçağ et al., 2020) However, lack of enrollment of patients with COVID‐19 pneumonia or lung involvement and controls before COVID‐19 infection were the main limitations of the above 2 studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, because both arterial and venous thromboses are common in COVID-19 cases, anticoagulation should be given as in our cases. The current literature reports that patients diagnosed as having acute fulminant myocarditis and cytokine syndrome, most likely resulting from SARS-CoV-2 infection, can be treated with tocilizumab, intravenous immunoglobulin, and high-dose corticosteroids even though results regarding this issue are conflicting (4,8,9). Lastly, patients with acute fulminant myocarditis due to COVID-19 who are resistant to medical therapy can be treated with extracorporeal membrane oxygenation support (10).…”
Section: Discussionmentioning
confidence: 99%
“…PCT was elevated on 0.53%, similar to Oleszak"s study on 1.95% [6,9,10] . As myocardium injured in myocarditis, cardiac enzymes are usually elevated from baseline, including troponin, N-terminal pro-B-type natriuretic peptide (NT-pro BNP) and BNP [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] . Cardiac biomarker was also elevated in our case with CKMB 9.6 ng/ml (n<4.3 ng/ml) similar to Fereirra"s study.…”
Section: Discussionmentioning
confidence: 99%